Pemanfaatan Linguistik Korpus dalam Menentukan Kata Berfrekuensi Tinggi pada Buku Sahabatku Indonesia BIPA 1 - Diyah Wahyuningtyas; Tri Mastoyo Jati Kesuma (Badan Pengembangan dan Pembinaan Bahasa, 2021)
The purpose of writing this article is describing parts of speech ‘kelas kata’ in the book “Sahabatku Indonesia BIPA 1 Umum”. The parts of speech were analyzed using a tool-based corpus, namely AntConc. The aim of using AntConc is for deciding the frequent or word using on that book. The result of this research is shown (1) ten high frequency words in the book “Sahabatku Indonesia BIPA 1 Umum” is: dan (402); di (289); saya (219); yang (199); ada (159); ini (159); dengan (145); untuk (125); kegiatan (113); apa (106); and also (2) the frequency of occurrence of parts of speech is noun (4.783); verb (2.134); particle (1.756); adjektive (948); pronoun (923); adverb (415); numeral (207); dan clitic (10).